2008
DOI: 10.1111/j.1365-2443.2008.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt signaling as a key regulatory pathway for chondrocyte terminal differentiation

Abstract: Chondrogenesis is a well‐coordinated multi‐step differentiation process in which resting chondrocytes produce terminally differentiated hypertrophic chondrocytes through a proliferative stage. Here we show that phosphoinositide‐3 kinase (PI3K) and its major downstream molecule, Akt, a serine–threonine kinase, play pivotal roles in this process. Akt signaling was activated in resting and proliferative chondrocytes but was reduced during terminal differentiation. We adopted two chondrocyte differentiation system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
81
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 50 publications
11
81
0
Order By: Relevance
“…A possible explanation for this discrepancy is that delayed ossification in Akt knockout mice is caused by Akt deletion in osteoblasts or bone collar cells. Akt signaling enhances chondrocyte proliferation (Kita et al, 2008) and PI3K decreases apoptosis (Ulici et al, 2008), consistent with the phenotypes of 11Prom-Cre; Sox9 flox/flox mice. The effects on hypertrophy are controversial, as PI3K enhances hypertrophy (Fujita et al, 2004), whereas Akt signaling inhibits hypertrophy (Kita et al, 2008).…”
Section: Discussionsupporting
confidence: 51%
“…A possible explanation for this discrepancy is that delayed ossification in Akt knockout mice is caused by Akt deletion in osteoblasts or bone collar cells. Akt signaling enhances chondrocyte proliferation (Kita et al, 2008) and PI3K decreases apoptosis (Ulici et al, 2008), consistent with the phenotypes of 11Prom-Cre; Sox9 flox/flox mice. The effects on hypertrophy are controversial, as PI3K enhances hypertrophy (Fujita et al, 2004), whereas Akt signaling inhibits hypertrophy (Kita et al, 2008).…”
Section: Discussionsupporting
confidence: 51%
“…Of note, we observed that insulin alone promoted more intense deposition of cartilaginous matrix than either TGF-β3 or a combination of insulin/TGF-β3 did, indicating that insulin plays a more important role than TGF-β3 in inducing the synthesis and deposition of glycosaminoglycans. In agreement, activation of the direct downstream factor of insulin, AKT, has been reported to enhance the chondrogenic differentiation of chondroprogenitor cells or stem cells [Kita et al, 2008;Hara et al, 2015], whereas the chemical inhibition of AKT completely repressed chondrogenic differentiation of stem cells [Hara et al, 2015]. The effect of insulin was apparently independent of TGF-β3 signaling, because there was no alteration in Smad phosphorylation or in the expression of CCN2, a direct target gene of TGF-β3, after insulin treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Likewise, in a temporal analysis of the alterations caused by AA/b-GP during MC3T3-E1 differentiation [Zambuzzi et al, 2008b], we observed down-regulation of the ERK 1/2 and PI3K/Akt pathways followed by the activation of GSK3b. Previous reports have associated inhibition of the PI3K pathway with differentiation in B16 melanoma cells [Buscà et al, 1996], human promyelocytic HL60 leukemia cells [Peiretti et al, 2001], and the myogenic cell line C2C12 [Viñ als et al, 2002], as well as in chondrocyte terminal differentiation [Kita et al, 2008]. On the other hand, PI3K/Akt/GSK3b signaling pathway is one of the key players in the signaling of potent anabolic factors in bone.…”
Section: Discussionmentioning
confidence: 98%